Clinical impact of hepatitis delta virus coinfection on liver fibrosis in hepatitis B patients: a population-based study - Sisi Yang; Qiaofeng Ye; Yida Yang; Zhenxuan Ma (Virology Journal)
Abstract Background Evaluation of liver fibrosis appears to be easily overlooked in the clinic for the chronic Hepatitis D. Herein, we determine the Clinical Impact of liver fibrosis among HBsAg-positive/Anti-HDV positive US general adults. Methods Data were obtained from the National Health and Nutrition Examination Survey (NHANES) 1999–2020. Liver fibrosis was assessed by the Fibrosis-4 (FIB-4) and aspartate aminotransferase to platelet ratio index (APRI) score. To minimize confounding, propensity score matching (PSM) was applied to compare HBV/HDV-coinfected and HBV-monoinfected individuals. Results Out of 107,622 NHANES adults, 54,550 were tested for HBsAg and Anti-HDV, of whom 214 were identified as HBsAg-positive only, 50 were identified as HBsAg-positive/Anti-HDV-positive with available data for FIB-4/APRI. Mean APRI scores were 0.26 for the Non-Viral Hepatitis (NVH) group, 0.37 for the HBV group, and 0.42 for the HBV + HDV group. Corresponding mean FIB-4 scores were 1.07, 1.34, and 1.58, respectively. After PSM, HDV-infected individuals exhibited significantly higher fibrosis scores compared to HBV-positive individuals. Conclusion Hepatitis D is more severe than hepatitis B, with a higher propensity to progress to liver fibrosis. These findings highlight the importance of routine fibrosis screening in HBsAg-positive/anti-HDV-positive individuals to prevent advanced liver disease.